Perancangan UI Website untuk Optimalisasi Penjadwalan Layanan pada Bisnis Lucete Beauty - Widi Ayu Purwaningtyas; Anik Hanifatul Azizah (Lembaga Pengembangan Kinerja Dosen, 2026)
The use of technology to improve business operations, efficiency, and transparency is essential for companies that want to grow in today’s competitive environment. This is especially true in the beauty industry, which continues to attract high interest, particularly among women. Lucete Beauty is a beauty business that offers Eyelash Extension and Korean Manicure and Pedicure services and operates three stores located at Pluit Village Mall, Artha Gading Mall, and Green Sedayu Mall. Currently, Lucete Beauty still uses a manual scheduling system through spreadsheets that combine the schedules of all three stores into one file. This approach increases the risk of data input errors and double bookings, which can negatively affect operational effectiveness and customer satisfaction.To overcome these problems, a website-based system was designed using the Design Thinking method to optimize the service scheduling process. This method was selected to better understand user needs and to develop solutions that are relevant and user friendly. The proposed design is considered acceptable if the usability testing results show a score above 51.7 with an “OK” adjective rating, measured using the System Usability Scale (SUS). Therefore, implementing this system is expected to improve service quality, scheduling accuracy, operational efficiency, and overall business performance.